2017
DOI: 10.3390/rs9070640
|View full text |Cite
|
Sign up to set email alerts
|

Landsat-Based Trend Analysis of Lake Dynamics across Northern Permafrost Regions

Abstract: Lakes are a ubiquitous landscape feature in northern permafrost regions. They have a strong impact on carbon, energy and water fluxes and can be quite responsive to climate change. The monitoring of lake change in northern high latitudes, at a sufficiently accurate spatial and temporal resolution, is crucial for understanding the underlying processes driving lake change. To date, lake change studies in permafrost regions were based on a variety of different sources, image acquisition periods and single snapsho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
134
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(155 citation statements)
references
References 86 publications
3
134
0
Order By: Relevance
“…The vivid spectral information provided by Landsat TM/ETM+ images has been widely used for mapping water surface area [38][39][40]. The basic logic of these studies is to highlight the difference between water bodies and other objects through the calculation of water indexes [48].…”
Section: Water Surface Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…The vivid spectral information provided by Landsat TM/ETM+ images has been widely used for mapping water surface area [38][39][40]. The basic logic of these studies is to highlight the difference between water bodies and other objects through the calculation of water indexes [48].…”
Section: Water Surface Mappingmentioning
confidence: 99%
“…Landsat TM/ETM+ images, because of their high spatial resolution (30 m), have been widely used to monitor the variations of water surface area [38][39][40]. In total, 904 Landsat TM/ETM+ images from 1991 to 2016 were obtained from the USGS Glovis data archive (http://glovis.usgs.gov).…”
Section: Landsat Imagery For Water Surface Areamentioning
confidence: 99%
“…Some studies observed significant decreases in size and number, and some found increases in the number, as well as in the area of lakes [9,28,29]. Obviously, the results are ambiguous and the reasons for the discrepancies are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [9,10,13] have indicated that the NDWI [16], normalized difference vegetation index (NDVI) [17], and normalized difference moisture index (NDMI) [18] can be applied to regional-scale water detection, showing high performance in distinguishing water at different band ranges. The modified normalized-Difference Water Index (MNDWI) [19], which has been widely used to detect water, can differentiate water from soil and buildings.…”
Section: Indicesmentioning
confidence: 99%
See 1 more Smart Citation